2023
DOI: 10.1098/rspb.2023.0696
|View full text |Cite
|
Sign up to set email alerts
|

Dogs’ expectations about occlusion events: from expectancy violation to exploration

Christoph J. Völter,
Ana Tomašić,
Laura Nipperdey
et al.

Abstract: Previous research on human infants has shown that violations of basic physical regularities can stimulate exploration, which may represent a type of hypothesis testing aimed at acquiring knowledge about new causal relationships. In this study, we examined whether a similar connection between expectancy violation and exploration exists in nonhuman animals. Specifically, we investigated how dogs react to expectancy violations in the context of occlusion events. Throughout three experiments, dogs exhibited longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Seventh, the VOE paradigm can be used not only with human infants but also with nonhuman animals (henceforth animals). VOE tasks have been employed with a wide range of animals including birds, cats, chimpanzees, dogs, dolphins, elephants, lemurs, lions, meerkats, monkeys, and sea lions, some tested in the wild and others in the laboratory (Drayton & Santos, 2018; Gilfillan et al, 2016; Singer & Henderson, 2015; Takagi et al, 2016; Völter et al, 2023; for reviews, see Ginnobili & Olmos, 2021; Winters et al, 2015). Total looking time is often used to measure animals’ surprise, but pupil dilation, exploration, and vigilance are also used.…”
Section: Strengths Of the Voe Paradigmmentioning
confidence: 99%
“…Seventh, the VOE paradigm can be used not only with human infants but also with nonhuman animals (henceforth animals). VOE tasks have been employed with a wide range of animals including birds, cats, chimpanzees, dogs, dolphins, elephants, lemurs, lions, meerkats, monkeys, and sea lions, some tested in the wild and others in the laboratory (Drayton & Santos, 2018; Gilfillan et al, 2016; Singer & Henderson, 2015; Takagi et al, 2016; Völter et al, 2023; for reviews, see Ginnobili & Olmos, 2021; Winters et al, 2015). Total looking time is often used to measure animals’ surprise, but pupil dilation, exploration, and vigilance are also used.…”
Section: Strengths Of the Voe Paradigmmentioning
confidence: 99%
“…Further, since a first understanding of the areas active when dogs see agents or actions is now established, investigations using more complex visual stimuli to study higherorder socio-cognitive skills can now be undertaken. Behavioural research has already shown that dogs have remarkable imitation skills (see e.g., Fugazza et al, 2023;Huber et al, 2020;Range et al, 2007), that they form expectations about their physical and social environment (see e.g., Lonardo et al, 2021;Schünemann et al, 2021;Virányi et al, 2006;Völter, Lonardo, et al, 2023;Völter, Tomašić, et al, 2023;Völter & Huber, 2021a, 2021b or even perform visual perspective taking (Catala et al, 2017;Maginnity & Grace, 2014;and see Huber & Lonardo, 2023 for review), but the neural bases of these visual analogous socio-cognitive skills with humans still remain largely unstudied.…”
Section: Future Directionsmentioning
confidence: 99%
“…Unlike rhesus macaques, dogs can match actions in a "Do-as-I-do" training paradigm (Fugazza et al, 2019;Fugazza & Miklósi, 2014;Topál et al, 2006), they spontaneously match human actions already as puppies (Fugazza et al, 2023), and even over-imitate action sequences demonstrated by their human caregivers (Huber et al, 2018(Huber et al, , 2020. Furthermore, dogs also share more complex socio-cognitive abilities with humans: they can perform visual perspective taking (Catala et al, 2017;Maginnity & Grace, 2014; and see Huber & Lonardo, 2023 for review), respond to unfair treatment (i.e., inequity aversion; Brucks et al, 2016;Essler et al, 2017;Range et al, 2009;McGetrick & Range, 2018 for review), form expectations about physical events (Völter, Tomašić, et al, 2023;Völter & Huber, 2021a, 2021b and are sensitive to humans' intentions, knowledge or beliefs (Lonardo et al, 2021;Schünemann et al, 2021;Virányi et al, 2006;Völter, Lonardo, et al, 2023). Finally, dogs and humans also display relevant differences in their abilities and behaviours, apart from unique human abilities such as language.…”
Section: Introductionmentioning
confidence: 99%